2002
DOI: 10.1046/j.1471-4159.2002.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

High transcytosis of melanotransferrin (P97) across the blood–brain barrier

Abstract: The blood-brain barrier (BBB) performs a neuroprotective function by tightly controlling access to the brain; consequently it also impedes access of proteins as well as pharmacological agents to cerebral tissues. We demonstrate here that recombinant human melanotransferrin (P97) is highly accumulated into the mouse brain following intravenous injection and in situ brain perfusion. Moreover, P97 transcytosis across bovine brain capillary endothelial cell (BBCEC) monolayers is at least 14-fold higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
126
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(133 citation statements)
references
References 41 publications
6
126
0
1
Order By: Relevance
“…This temperature dependence was demonstrated for recombinant MTf transcytosis. 11 To confirm Ad5 vectors were indeed transported across the endothelial barrier via transcytosis pathway, we examined temperature dependence of this process by performing the transcytosis assay at either 4 or 371C. As shown in Figure 4a, sCAR-MTf-mediated transcytosis was completely inhibited at 41C (Po0.01), whereas in the control experiment with sCAR, there was no significant difference between 4 and 371C (P40.05).…”
Section: Temperature-dependence Of Scar-mtf-mediated Ad5 Transcytosismentioning
confidence: 95%
See 4 more Smart Citations
“…This temperature dependence was demonstrated for recombinant MTf transcytosis. 11 To confirm Ad5 vectors were indeed transported across the endothelial barrier via transcytosis pathway, we examined temperature dependence of this process by performing the transcytosis assay at either 4 or 371C. As shown in Figure 4a, sCAR-MTf-mediated transcytosis was completely inhibited at 41C (Po0.01), whereas in the control experiment with sCAR, there was no significant difference between 4 and 371C (P40.05).…”
Section: Temperature-dependence Of Scar-mtf-mediated Ad5 Transcytosismentioning
confidence: 95%
“…As previous studies have shown that MTf prefers apical-to-basal transcellular transport, 11 in the transcytosis assay, we pre-mixed Ad5 VPs with sCAR-MTf or control sCAR, and added the complexes to the upper chamber (apical side of the barrier). The cells were then sCAR-MTf-mediated Ad5 transcytosis across the BBB Y Tang et al incubated for 6 h in a 371C, 5% CO 2 -containing humidified incubator to allow transcytosis to occur.…”
Section: Ad5 Transcytosis Mediated By Scar-mtfmentioning
confidence: 99%
See 3 more Smart Citations